Talent Management Aparatur Sipil Negara (ASN) Era Digitalisasi Birokrasi di Indonesia: Talent Management of civil servant (ASN) era of Bureaucratic digitalization in Indonesia (Administratio, 2020)
Sustainability and competitive advantage of an organization are very dependent on human resources that can compete with changes that are all digitizing. The Industrial Revolution 4.0 has changed the Direction of Talent Management in creating ASN in the future to facilitate complex digital-based public services. The purpose of this study is to discuss the substance of talent management and competency-related issues using concepts related to Industry 4.0. Talent management has an interest in the organization, because it gives an opportunity to recruit, support and develop the talent that is need and then developed as a future player which is a combination of cyber-physical systems. This new technology will affect all cross-disciplines and even oppose human resources, how Industry 4.0 will change the land-scape for talent development. The research method used is a qualitative method. Data collection done through the collection, interview and documentation of informants who are directly involved in carrying out these activities. The process of data analysis adds data reduction, data presentation, and completes conclusions. The results showed that (1) the abilities needed in talent management in the 4.0 era were positive abilities, technical abilities and complex problem solving skills; (2) Basic ICT skills are need to be move to the digitalisation era.